Thinking and Managing: A Verbal Protocol Analysis of Managerial Problem Solving - Isenberg, Daniel J. (Academy of Management Journal, 1986)
While thinking aloud, 12 general managers from six corporations solved a short business case. Three college undergraduates performed the identical task. Content analyses of the verbal protocols suggested that the managers began planning courses of action relatively sooner, used more reasoning processes, and made fewer requests for specific information than did the students. Correlations with independent ratings of the effectiveness of action plans suggested that those managers who employed analogical reasoning and whose recommendations were specific generated better action plans than other managers. These findings are discussed in terms of a model of opportunistic thinking.